2020
DOI: 10.1177/1756284820923904
|View full text |Cite
|
Sign up to set email alerts
|

Plasma eicosanoids as noninvasive biomarkers of liver fibrosis in patients with nonalcoholic steatohepatitis

Abstract: Background: Eicosanoid and related docosanoid polyunsaturated fatty acids (PUFAs) and their oxygenated derivatives have been proposed as noninvasive lipidomic biomarkers of nonalcoholic steatohepatitis (NASH). Therefore, we investigated associations between plasma eicosanoids and liver fibrosis to evaluate their utility in diagnosing and monitoring NASH-related fibrosis. Methods: Our analysis used baseline eicosanoid data from 427 patients with biopsy-confirmed nonalcoholic fatty liver disease (NAFLD), and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The observed fatty acid composition changes were grosso modo comparable for both organs, yet the absolute omega-3 PUFA concentrations per milligram of tissue were clearly higher in the liver. Importantly, a refined oxylipin LC-MS/MS analysis showed that KrO strongly increased lipid species with anti-inflammatory properties [ 35 , 36 , 37 ] derived from EPA and DHA (e.g., 18-HEPE, RvE 2 , 14-HDHA, 17-HDHA, PDX/10S,17S-diHDHA), whereas it suppressed the HFD-induced formation of ARA-derived oxylipins (e.g., HETEs, PGD 2 , PGE 2 , PGF 2 and TXB 2 ), which often exert pro-inflammatory effects [ 37 , 38 , 39 , 40 , 41 ]. Notably, the results of the two independent lipidomics approaches employed herein (the fatty acid composition analysis and the oxylipin analyses) were in line with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The observed fatty acid composition changes were grosso modo comparable for both organs, yet the absolute omega-3 PUFA concentrations per milligram of tissue were clearly higher in the liver. Importantly, a refined oxylipin LC-MS/MS analysis showed that KrO strongly increased lipid species with anti-inflammatory properties [ 35 , 36 , 37 ] derived from EPA and DHA (e.g., 18-HEPE, RvE 2 , 14-HDHA, 17-HDHA, PDX/10S,17S-diHDHA), whereas it suppressed the HFD-induced formation of ARA-derived oxylipins (e.g., HETEs, PGD 2 , PGE 2 , PGF 2 and TXB 2 ), which often exert pro-inflammatory effects [ 37 , 38 , 39 , 40 , 41 ]. Notably, the results of the two independent lipidomics approaches employed herein (the fatty acid composition analysis and the oxylipin analyses) were in line with each other.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to partially converted into EPA, n-3 DPA and DHA (with low conversion rate to DHA in human) ( de Lorgeril and Salen, 2004 ; Stark et al, 2008 , 2016 ), the effects of oxylipins derived from ALA by LOX and CYP have also gained attention. Recently, a clinical research showed that 9-hydroxy-octadecatrienoic acid (9-HOTRE) combined with 7,17dihydro-dipicolinic acid (7,17-DHDPA), 14,15-dihydroxy-5,8,11-eicosatrienoic acid (14,15-DIHETRE) and free adrenic acid is a biomarker to predict improvement in hepatic collagen content in NASH patients ( Caussy et al, 2020 ). Besides, in obese rats, 9-HOTRE showed a negative correlation with mean glomerular volume ( Caligiuri et al, 2013 ).…”
Section: Effect Of Ala and Its Derivatives On Metabolic Disordersmentioning
confidence: 99%
“…Mice are sensitized to liver injury through oxysterols (cholesterol-derived products) and lipid mediators derived from arachidonic acid (e.g., eicosanoids), resulting in proinflammatory and profibrogenic effects [ 117 , 118 , 119 ]. The pathogenic role of these lipids in the course of NASH and fibrosis is currently under investigation [ 120 ]. Conversely, oxylipins (proinflammatory products of PUFA metabolism) are increased in plasma of NAFLD patients but are not responsive to gut-derived immunogens [ 121 ].…”
Section: Can Lipidomics Provide Insights Into the Pathogenesis Of mentioning
confidence: 99%